Access first contact in primary health attention for children - Beatriz Rosana Gonçalves de Oliveira; Cláudia Silveira Viera; Neusa Collet; Regina Aparecida Garcia de Lima (Universidade Federal do Ceará, 2012)
The study aimed to identify the access at the first contact, one of the principles at the primary health attention, in public health unit, for children under five years with respiratory problems. It was a qualitative study, performed by hermeneutic language, whose conceptual basis is centered on care. The empirical part consists of interviews with companions of the hospitalized children and health professionals from primary care units and emergency. The understanding of the data by hermeneutic language guides the analysis. The results show that access to first contact is occurring in emergency care for acute episodes of health problems instead of the primary care units, without programmatic actions and advisement as a method of the daily action, as well as the primary health attention does not act as regulator of the health system, requiring of the reflection on its role as part of health services and the resumption of its function.